The Effects of Social Media on Motivating Second Language Learners - Nanda Finka Sabila; Lusiana Suciati Dewi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The research aims to explore the effects of using social media in second language learning. In today’s digital era, social media has become a significant tool in various aspect of life, including education. This research uses qualitative methods with in-depth interviews and observations to collect data from 30 high school (high school) student who are learning a second language through social media platforms such as Instagram, twitter, ticktock, and YouTube.The result of the study showed that the use of social media in second language learning had a positive impact on the participants communication skills. Social media allows access to a variety of authentic sources and the opportunity to interact with native speakers, which in turn improves language skills significantly. In addition, participants increased motivating and confidence in using the second language.